Role of Dietary Antioxidants in the Preservation of Vascular Function and the Modulation of Health and Disease - Varadharaj, Saradhadevi; Kelly, Owen J.; Khayat, Rami N.; Kumar, Purnima S.; Ahmed, Naseer; Zweier, Jay L. (Frontiers in Cardiovascular Medicine, 2017)
In vascular diseases, including hypertension and atherosclerosis, vascular endothelial dysfunction (VED) occurs secondary to altered function of endothelial nitric oxide synthase (eNOS). A novel redox regulated pathway was identified through which eNOS is uncoupled due to S-glutathionylation of critical cysteine residues, resulting in superoxide free radical formation instead of the vasodilator molecule, nitric oxide (NO). In addition, the redox sensitive cofactor tetrahydrobiopterin, BH4, is also essential for eNOS coupling. Antioxidants, either individually or combined, can modulate eNOS uncoupling by scavenging free radicals or impairing specific radical generating pathways, thus preventing oxidative stress and ameliorating VED. Epidemiological evidence and dietary guidelines suggest that diets high in antioxidants, or antioxidant supplementation, could preserve the vascular health and prevent cardiovascular diseases (CVD). Therefore, the purpose of this review is to highlight the possible role of dietary antioxidants in regulating eNOS function and uncoupling which is critical for maintenance of the vascular health with normal blood flow/circulation and prevention of VED. We hypothesize that a conditioned dietary approach with suitable antioxidants may limit systemic oxidation, maintain a beneficial ratio of reduced to oxidized glutathione, and other redox markers, and minimize eNOS uncoupling serving to prevent CVD and possibly other chronic diseases.